PESANTREN AND MULTIPLE INTELLIGENCES: OPPORTUNITIES AND OBSTACLES OF PESANTREN IN DEVELOPING THE EIGHT INTELLIGENCES - Aldi Hidayat; Ilfan Tufail (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2024)
This research seeks to reveal the hidden side of the oldest Islamic educational in Indonesia, namely pesantren. As an agency that operates with culture that is unique, with movement that run within the Islamic religious system. Pesantren with this position are often referred to as the first mosaic of Islamic civilization in the country. This research uses a qualitative approach with the type of library reseach, by collecting data sources from existing literature. Various facts and realities that are not widely disclosed by several educational researchers and observers, often become the starting point for the growth of slanted understanding from a handful of opinions that question the contribution of pesantren to our motherland. The researchers tried to answer this question by analyzing the phenomena that exist in pesantren, especially the educational system and patterns that run in pesantren in forming and preparing students (santri) with the diversity of potential that exist within them. Keyword: Pesantren; multiple intelligence; Islamic education, opportunities, obstacles.